Мікориза сосни кедрової європейської (Pinus cembra L.) - Sirenko, O.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The morphological and anatomic structure of European cedar pine mycorhiza in various coenotical conditions is introdused. The results of investigations of ground mycorhiza influence on European cedar pine seedlings are given.